Community Adaptation to Climate Change in Ulukhaktok, Canada - Pearce, T; Smit, B; Duerden, F; Goose, A; Inuktalik, R; Kataoyak, F (2008)
This paper presents research that examined the sensitivity and adaptive capacity of people and their livelihoods to climate change in Ulukhaktok, NWT, Canada. The case study identifies climate conditions and hazards that community members are currently dealing with, the adaptive strategies employed to deal with these hazards, the effectiveness of these adaptive strategies and the capacity of the community to deal with future climate change. As a result of climate-driven changes and changing livelihoods, community members in Ulukhaktok are sensitive to climate hazards associated with harvesting activities including, travel routes on the sea-ice, land and ocean, and changes in the health and distribution of wildlife species important for subsistence. These changes have implications for food security, household income, health and culture. Community members are currently demonstrating significant adaptability to changing conditions by harvesting alternative species of wildlife, being flexible in harvesting activities (e.g. timing, travel routes), using technologies (e.g. GPS, VHF radio, weather forecasts) to ensure safe travel, and supplementing country foods with store-bought foods. However, the capacity to adapt differs amongst community members as does the desirability of adaptation options. Institutional support (e.g. financial aid and harvesting resources) and social networks (e.g. food sharing, knowledge sharing, equipment sharing) are identified as key components of adaptive capacity. These sources provide strategic opportunities to integrate adaptation planning to climate change within existing institutions and community networks.